Accuration of Fine Needle Aspiration Biopsy in Musculoskeletal Tumour - Rahadyan Magetsari; Hengkie Marseno; Zikrina Lanodiyu; Punto Dewo (International Journal of Public Health Science (IJPHS), 2016)
Fine needle aspiration biopsy (FNAB) has been reported to be the preferable choice of biopsy for musculoskeletal tumour. While FNAB appears to have advantages to core biopsy in the aspect of simplicity and cost, the diagnostic accuracy should be the most critical parameter in determining the choice of biopsy. This research was designed to evaluate the diagnostic accuracy of fine needle aspiration in musculoskeletal tumour in Sardjito Hospital from 2010 until 2014. This was a descriptive study from medical record in Sardjito Hospital from 2010 until 2014. The inclusion criteria are musculoskeletal tumours in all age level that has been performed FNAB with subsequent operative treatment and confirmation of histopathology examination in Sardjito Hospital. There were 41 elligible subjects in this study. Concordance diagnosis of FNAB and histopathological examination in all musculoskeletal tumor cases was found to be 86%. In addition, the concordance in soft tissue tumor cases was 94% with the detail as follows: giant cell tumor was 86%, synovial sarcoma was 50% and liposarcoma was 50%. In bone tumours, the accuracy was found to be 60% with the detail as follows: distribute osteosarcoma was 60%, osteochondroma was 50% and chondrosarcoma was 50%. Our data showed that accuracy of FNAB for diagnosis of musculoskeletal tumours was 86% with soft tissue tumour 94%, bone tumour 60% and others 93%. Therefore, Fine needle aspiration biopsy is still important diagnosis tool in musculoskeletal tumours.